Analysis of farmers’ participatory research on mite management in coconut in Bangladesh - M. Sayedur Rahman, M. Nazirul Islam; M. Samsunnahar, M. Ishaqul Islam; A.N.M Rezaul Karim, A.K. Azad (Journal of Plantation Crops, 2017)
-